Manajemen Pendidikan Islam Prespektif Pedadogik dan Andragogik - Tharaba, M. Fahim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Management of Islamic Education analysis of Pedadogic and andragogic theory departs from How Islam sees, teaches, instills and embodies his people's education in order to build independent generations through the concept of preparation and travel processes Pedagogic school, to be a total self-reliant with the concept of Perkepribadian conscious and self-reliant andragogy. From the results of the analysis, Islam, build civilization started from choosing a match (education). Subsequently, the education was directed and Dimanaj in order to print (???? ??? ????), in this case, was pre, primary and secondary education. To be subsequently directed in achieving degrees (?????), and this was achieved perfectly through undergraduate education (S-1/Bachelor's degree), even the Derjat (?????) was further enhanced through graduate education of strata Two (S-2/Magister) and the peak was (????) achieved with the education in strata Three (S-3/doctoral). And the highest degree (????) is perfected with the degree of Professor in any field/profession.